Improving Farmed Juvenile Gilthead Seabream (Sparus aurata) Stress Response to Marine Heatwaves and Vibriosis Through Seaweed-Based Dietary Modulation - Alícia Pereira; Isa Marmelo; Tomás Chainho; Daniel Bolotas; Marta Dias; Rui Cereja; Marisa Barata; Pedro Pousão-Ferreira; Elsa F. Vieira; Cristina Delerue-Matos; Mário S. Diniz; António Marques; et al. (Animals)
Marine heatwaves (MHWs) are an emerging challenge for aquaculture, increasing the frequency and severity of disease outbreaks in farmed fish, weakening immunocompetence and compromising overall health and survival. As climate change stressors intensify, there is an urgent need for cost-effective and environmentally friendly strategies to enhance fish resilience. This study investigated the efficacy of Laminaria digitata, a brown macroalga, included in aquafeeds as powder (0.3% and 1.5%) or extract (0.3%) in improving the stress response of juvenile gilthead seabream (Sparus aurata) co-exposed to Vibrio harveyi infection during a category III MHW event. Under control conditions, L. digitata supplementation maintained or improved fish growth performance and overall well-being. After MHW exposure, the 1.5% powdered and 0.3% extract diets were more effective in mitigating thermal stress, reducing liver oxidative stress and lowering plasma cortisol levels. In infected fish, these diets improved resistance to V. harveyi, with reduced cortisol and alanine aminotransferase concentrations indicating hepatoprotective properties, and lower lipid peroxidation and decreased antioxidant enzyme activities reflecting an amplified capacity to counteract oxidative stress induced by inflammation. Overall, L. digitata is a promising aquafeed supplement, with the 1.5% powdered form offering a cost-effective alternative to the extract without compromising efficacy.